The relationship of husband's knowledge and attitude to male operating method contraception participation at Ujung Padang health center, Simalungun district - Beta Hanindiya; Nurasima Kurniati Damanik (Science Midwifery, 2022)
The Family Planning Program (KB) is one of the government's efforts to achieve family welfare. The family planning program is an integrated part of the national development program which aims to achieve balanced population growth so that the economic, spiritual and socio-cultural welfare of the Indonesian population can be achieved with a Total Fertility Rate (TFR) of 2.2. The Male Operation Method (MOP) is the act of cutting and closing the seminal canals (vas deferens) that channel sperm cells (sperm) out of their reproductive centers in the testicles. The purpose of this study was to determine the relationship between knowledge and attitudes of husbands towards participation in male contraceptive methods (MOP) at the Ujung Padang District Health Center, Simalungun Regency in 2016. The type of this study was analytic. The population of this study were husbands of fertile couples. The sample in this study were all husbands who visited the Ujung Padang Health Center. The results of the research based on the results of the Chi-Square statistical test obtained p value = 0.03 alpha 0.05. So that it is known that there is a relationship between husband's knowledge of male contraceptive participation. Based on the results of the Chi-Square statistical test, p value = 0.05 alpha 0.05 was obtained. So that it is known that there is a relationship between the husband's attitude towards the participation of male contraceptive methods (MOP). It is hoped that the results of the research can become input and suggestions for health workers at the Ujung Padang Health Center in maintaining and improving MOP family planning services in the community.